(untitled) (Comprehensive Journal of Science, 2026)
This research aims to examine the impact of Artificial Intelligence (AI) on national security policies in light of the rapid digital transformations taking place in the contemporary world. AI has become one of the most influential tools in shaping the strategic power of states, while at the same time creating new and complex security threats. The study discusses the concept of AI, its development, and its relationship with national security across its political, military, economic, social, and cyber dimensions, with a particular focus on how AI is reshaping the nature of modern security threats. The research also explores the growing role of AI in enhancing military and intelligence capabilities, improving surveillance and analytical processes, and supporting security decision-making. In addition, it highlights the use of AI in smart defense systems, unmanned aerial vehicles (UAVs), and big data analysis to detect threats at an early stage. On the other hand, the study emphasizes the risks AI poses to national security, including advanced cyberattacks, deepfake technology, information warfare, and attacks on critical infrastructure, which may threaten political and social stability. Furthermore, the research addresses the legal and ethical challenges arising from the use of AI in security fields, particularly issues related to privacy violations, the expansion of digital surveillance, the lack of regulatory legislation, and the problem of legal responsibility when decisions are made by intelligent systems. The study concludes that AI represents a double-edged sword: it contributes to strengthening national security on one hand, while generating unconventional security threats on the other. Therefore, it is necessary to adopt comprehensive national strategies to regulate AI usage, enhance cybersecurity systems, promote international cooperation, and establish legal and ethical frameworks to ensure the safe and responsible use of this technology.